Pemberdayaan Masyarakat Dan Peningkatan Kualitas Pendidikan Desa Tanjung Tiram Tahun 2023 - Fadli Muhammad; Indra Divari Lubis; Ridwan Alwi Nasution; Maulinda Maulinda; Nur Saidah Nasution; Riski Annisa Nasution; Tri Indah Rahmadhani; Nadya Annisa Lubis; Ummu Salama Parinduri (Institut Nalanda, 2024)
The community service carried out by KKN students at the Mandailing Natal State Islamic College group 39 which was carried out from 03 June 2023 to 22 August 2023 at Tanjung Tiram Village, Padang Bolak District, North Padang Lawas Regency has provided the community with an example that is very meaningful for the community in particular Tanjung Tiram Village area and received a good response and high enthusiasm. The work program that we carried out while we were in Tanjung Tiram Village was very focused on education problems in Tanjung Tiram Village because lack of interest in learning and lack of motivation were the main problems faced by students in Tanjung Tiram Village, so we held a tutoring program, with this tutoring program. will increase interest in learning and knowledge in the children of Tanjung Tiram village. The supporting factors regarding interest and motivation to learn include: the desire and enthusiasm to learn is still present in every child, the feeling of wanting to change and become a better person is very visible, and The shortcomings in society are already improvements that we have to make as KKN students at the Mandailing Natal Community Service Group 39, Tanjung Tiram Village, Padang Alley District, North Padang Lawas Regency. The research method used is descriptive qualitative. Based on the research results, this tutoring activity has a significant impact in terms of general knowledge so that the quality of education and students' awareness of learning continues to increase.